Synthesis, characterization of cellulose acetate membrane and application for the treatment of oily wastewater - Shoba, B (Environmental technology, 2020)
This study reports the synthesis of cellulose acetate (CA) membranes of different weight percentages of the polymer ranging from 5 to 17.5 wt% with 2.5% increment and their behaviour towards oil removal from water. The membrane showed decreased water content and porosity and also increased hydraulic resistance upto 3.38 kPa/(l m-2 h-1) as the concentration of polymer increases. The Atomic Force Microscopic studies reveal that the membrane shows decreased arithmetic mean roughness from 36.291 to 5.935 nm as the concentration of the polymer increases from 5% to 17.5%. Field Emission Scanning Electron Microscopy shows the surface morphology of the CA membrane. X-ray diffraction studies indicate that in the membrane having above 15% polymer concentration, the polymer chains orient to regularity showing higher crystallinity. The thermal studies indicate their stability upto 280°C, and exothermic decompositions from 338°C to 380°C implying the compactness of chains as polymer concentration increases. From Total Organic Carbon studies, the oil rejection was found to be maximum (96.4%) for the highest concentration of polymer in the membrane